A new species of Impatiens (Balsaminaceae) from Eravikulam National Park, southern Western Ghats, India. Issue 2 (3rd July 2019) - Salish, Menachery Johnson; Hareesh, Vadakkoot Sankaran; Arun, Lekshmi; Sandeep, Sukesan; Rajan, Pilakandy
ABSTRACT: Impatiens eravikulamensis, a new species of Impatiens from Idukki district of Kerala, southern Western Ghats is described. Detailed descriptions, distribution and ecology along with photographs are provided.